Given :

Let scores be s1,s2,s3

\(s3 = 1,6 (\frac{s1}{2}+ \frac{s2}{2})\)

(1) rearranging this :

\(s1+s2 = \frac{5}{4}*s3\)

(2) Average of 3 score is =

\(\frac{1}{3}*(s1+s2+s3)\)

We can use the information at (1) to replace \(s1+s2\) into equation (2)

\(Average =\frac{1}{3} * ( \frac{5}{4}*s3 +s3)\)

\(Average = \frac{1}{3} * ( \frac{9}{4}*s3)\)

\(Average = \frac{3}{4}*s3\)

\(s3 = \frac{4}{3}*Average\)

\(s3 = 1.33333 * Average\)

making s3 133% of the Average

Answer D _________________

Kudos (+1) if you find this post helpful.